2013
DOI: 10.1073/pnas.1220589110
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for participation of the methionine sulfoxide reductase repair system in plant seed longevity

Abstract: Seeds are in a natural oxidative context leading to protein oxidation. Although inevitable for proper progression from maturation to germination, protein oxidation at high levels is detrimental and associated with seed aging. Oxidation of methionine to methionine sulfoxide is a common form of damage observed during aging in all organisms. This damage is reversible through the action of methionine sulfoxide reductases (MSRs), which play key roles in lifespan control in yeast and animal cells. To investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
106
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 65 publications
4
106
0
2
Order By: Relevance
“…Most mutants in seed longevity are of two types: recessive mutants, with poor longevity affected in genes required for seed development (such as lec1, lec2, fus3, and abi3; Holdsworth et al, 1999;Clerkx et al, 2003Clerkx et al, , 2004, and dominant mutants, with improved longevity obtained by reverse genetics overexpressing stress defenses and repair systems such as small heat shock proteins (Prieto-Dapena et al, 2006), Met sulfoxide reductase (Châtelain et al, 2013), DNA glycosylase/AP lyase (Chen et al, 2012), and L-isoaspartyl methyltransferase (Ogé et al, 2008). To our knowledge, our athb25-1D mutant is the first mutant obtained by forward genetics and the first dominant mutant not related Figure 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most mutants in seed longevity are of two types: recessive mutants, with poor longevity affected in genes required for seed development (such as lec1, lec2, fus3, and abi3; Holdsworth et al, 1999;Clerkx et al, 2003Clerkx et al, , 2004, and dominant mutants, with improved longevity obtained by reverse genetics overexpressing stress defenses and repair systems such as small heat shock proteins (Prieto-Dapena et al, 2006), Met sulfoxide reductase (Châtelain et al, 2013), DNA glycosylase/AP lyase (Chen et al, 2012), and L-isoaspartyl methyltransferase (Ogé et al, 2008). To our knowledge, our athb25-1D mutant is the first mutant obtained by forward genetics and the first dominant mutant not related Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species induce lipid oxidation, and Arabidopsis (Arabidopsis thaliana) mutants (vitamin E deficient1 and vitamin E deficient2) affected in the biosynthesis of vitamin E (tocopherol, a lipophilic antioxidant) produce seeds with reduced longevity (Sattler et al, 2004). Repair of oxidized proteins by Met sulfoxide reductase (Châtelain et al, 2013), of oxidized DNA by DNA glycosylase/ Apurinic/Apyrimidinic lyase (Chen et al, 2012), and of chemically degraded proteins by L-isoaspartyl methyltransferase (Ogé et al, 2008) enhances seed longevity. Other important factors are chaperones or heat shock proteins.…”
mentioning
confidence: 99%
“…Two DNA repair enzymes, AtLIG6 and AtOGG1, repair DNA damage in seeds under stress, thus extending seed longevity (Chen et al 2012;Waterworth et al 2010). Another important protein repair system, the methionine sulfoxide reductase repair system, has recently been shown to play a key role in the establishment and preservation of seed longevity (Chatelain et al 2013). These findings draw attention to the role of the plant's own repair systems and their effects on seed longevity and germination vigor.…”
Section: Discussionmentioning
confidence: 99%
“…Plant seeds have a very low metabolic activity and resource use capability, which means that protein de-novo synthesis almost ceases (Rajjou et al 2012). To achieve homeostasis when exposed to aging, seeds use repair systems that have a low resource and energy cost to alleviate and repair damage without de-novo synthesis (Chatelain et al 2013;Oge et al 2008;Verma et al 2013). Spontaneous formation of abnormal isoaspartyl (isoAsp) residues from Laspartyl or L-asparaginyl residues in proteins is a common form of protein covalent damage in cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…ROS readily oxidizes Met residues in proteins/peptides to form Met-Rsulfoxide or Met-S-sulfoxide, resulting in the inactivation or malfunction of the proteins. Methionine sulfoxide reductases catalyzes the reduction of methionine sulfoxide (MetSO) to methionine in proteins and plays a protective role against oxidative stress by restoring activity to proteins that have been inactivated by methionine oxidation [27,28,29,30]. Swarupa et al [31] reported current research on oxidative burst and antioxidant enzymes, i.e.…”
Section: Discussionmentioning
confidence: 99%